2022
DOI: 10.21608/mjapfp.2022.263865
|View full text |Cite
|
Sign up to set email alerts
|

Maturity and Gonadosomatic Index of European Hake Merluccius Merluccius (Linnaeus, 1758) From the Egyptian Mediterranean Water

Abstract: Looking at the Mediterranean in particular, we find that its production decreased during the ten years from 77,799 tonnes in 2011 to 49,896 tonnes in 2020, and the quantities produced by some common fish families of economic and nutritional importance also decreased. Especially benthic fish, which are of great importance, especially for residents of coastal cities in the Egyptian country, such as bourbon fish, whose production decreased from 4,124 tonnes in 2011 to only 549 tonnes in 2020, and shrimp productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…The highest reproductive intensity in this study was observed during spring followed by winter. A number of studies in the region have reported spawning between November and March, including the Mediterranean coastline in Egypt [23], Central, and Western Mediterranean [21], the Sea of Marmara Turkey [11], and the Atlantic Moroccan coast [52]. Spawning season can be affected by several factors including temperature, food availability, and the condition factor [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest reproductive intensity in this study was observed during spring followed by winter. A number of studies in the region have reported spawning between November and March, including the Mediterranean coastline in Egypt [23], Central, and Western Mediterranean [21], the Sea of Marmara Turkey [11], and the Atlantic Moroccan coast [52]. Spawning season can be affected by several factors including temperature, food availability, and the condition factor [55].…”
Section: Discussionmentioning
confidence: 99%
“…Hake landings in Hellenic waters between 1992 and 2022 exhibited a declining trend, with an annual mean of 4,107 ± 889 tons [14] with Aegean catches representing on average (2010-2020) 81% the of the total Hellenic catches [15]. A fact of concern is that numerous reports indicate that the length at first maturity (L50) is higher than 20 cm [10,[16][17][18][19][20][21][22][23] which is the minimum landing size (MLS) in the Mediterranean, whereas the MLS in effect for hake populations of the Atlantic and North Sea is between 27 and 30 cm [24].…”
Section: Introductionmentioning
confidence: 99%